Assessing preschoolers interactive behaviour: a validation study of the “Coding System for Mother–Child Interaction” - Baiao, Rita (2018)
Background: The preschool years are a period of great developmental achievements, which impact critically on a child's interactive skills. Having valid and reliable measures to assess interactive behaviour at this stage is therefore crucial. The aim of this study was to describe the adaptation and validation of the child coding of the Coding System for Mother–Child Interactions and discuss its applications and implications in future research and practice. Methods: Two hundred twenty Portuguese preschoolers and their mothers were videotaped during a structured task. Child and mother interactive behaviours were coded based on the task. Maternal reports on the child's temperament and emotional and behaviour problems were also collected, along with family psychosocial information. Results: Interrater agreement was confirmed. The use of child Cooperation, Enthusiasm, and Negativity as subscales was supported by their correlations across tasks. Moreover, these subscales were correlated with each other, which supports the use of a global child interactive behaviour score. Convergent validity with a measure of emotional and behavioural problems (Child Behaviour Checklist 1 ½–5) was established, as well as divergent validity with a measure of temperament (Children's Behaviour Questionnaire–Short Form). Regarding associations with family variables, child interactive behaviour was only associated with maternal behaviour. Conclusions: Findings suggest that this coding system is a valid and reliable measure for assessing child interactive behaviour in preschool age children. It therefore represents an important alternative to this area of research and practice, with reduced costs and with more flexible training requirements. Attention should be given in future research to expanding this work to clinical populations and different age groups.